The effects of DPP-4 inhibitor on hypoxia-induced apoptosis in human umbilical vein endothelial cells - Akari Nagamine; Hiroshi Hasegawa; Naoko Hashimoto; Tomoko Yamada-Inagawa; Masanori Hirose; Yuka Kobara; Hiroyuki Tadokoro; Yoshio Kobayashi; Hiroyuki Takano (Elsevier, 2017)
Dipeptidyl peptidase-4 (DPP-4) inhibitors are a new class of oral hypoglycemic agents for patients with type 2 diabetes mellitus and have potential antiatherosclerotic properties. Meanwhile, it is unclear how DPP-4 inhibitors have protective effects on atherosclerosis. Our aim was to determine the effects and its mechanisms of DPP-4 inhibitors on cultured endothelial cells. Human umbilical vein endothelial cells (HUVECs) were cultured in hypoxic condition. To evaluate the protective effects of DPP-4 inhibitor on HUVECs, DPP-4 inhibitor was added in the cell culture medium and the cell viability was assessed by TUNEL assay. And we examined the intracellular signaling pathways in relation to the effects of DPP-4 inhibitor. DPP-4 inhibition had beneficial effects by inhibiting the apoptosis under hypoxic conditions in HUVECs. The antiapoptotic effects of DPP-4 inhibitor were abolished by the pretreatment with a CXCR4 antagonist or a Stat3 inhibitor. DPP-4 inhibition has beneficial effects on HUVECs by inhibiting the apoptosis under hypoxic conditions. SDF-1α/CXCR4/Stat3 pathways might be involved in the mechanisms of the cytoprotective effects of DPP-4 inhibitor. These results suggested that DPP-4 inhibitor has a potential for protecting vessels.